Impact of exercise training on oxidative stress in individuals with a spinal cord injury - van Duijnhoven, Noortje (Springer-Verlag, 2010)
Individuals with a spinal cord injury (SCI) have an increased cardiovascular risk. We hypothesize that (anti)oxidative imbalance is associated with the increased cardiovascular risk in SCI, while exercise can reverse this status. The aim of the study is to compare baseline levels of oxidative stress and antioxidative capacity between individuals with SCI and able-bodied (AB) subjects, and to assess acute and long-term effects of functional electrical stimulation (FES) exercise on oxidative stress and antioxidative capacity in SCI. Venous blood was taken from subjects with an SCI (n = 9) and age- and gender-matched AB subjects (n = 9) to examine oxidative stress through malondialdehyde (MDA) levels, while superoxide dismutase (SOD) and glutathione peroxidase (GPx) enzyme levels represented anti-oxidative capacity. Subsequently, subjects with an SCI performed an 8-week FES exercise training period. Blood was taken before and after the first exercise bout and after the last FES session to examine the acute and chronic effect of FES exercise, respectively. Baseline levels of MDA, SOD and GPx were not different between individuals with SCI and AB subjects. SCI demonstrated a correlation between initial fitness level and MDA (R = −0.83, P = 0.05). MDA, SOD and GPx levels were neither altered by a single FES exercise bout nor by 8 weeks FES training. In conclusion, although individuals with an SCI demonstrate a preserved (anti)oxidative status, the correlation between fitness level and (anti)oxidative balance suggests that higher fitness levels are related to improved (anti)oxidative status in SCI. Nonetheless, the FES exercise stimulus was insufficient to acutely or chronically change (anti)oxidative status in individuals with an SCI.